Agnes Slack and the Temperance Movement - Paisana, Joanne (2014)
This paper will focus on the pioneering work of Agnes E. Slack (1857-1946), one of a small group of upper class/aristocratic women who was active in the Temperance Movement in late Victorian / Edwardian Britain. Honorary Secretary of the British Women's Temperance Association (BWTA) and the World's Woman's Christian Temperance Union from 1895, the last President of the National British Women's Temperance Association (1925-6), and the first President of the National British Women's Total Abstinence Union (1926-8), she aimed to organize women to encourage temperance by education and other means, and to agitate for the restriction of sales of alcohol. She was a tireless organizer and effective public speaker not only on behalf of temperance but also for the Liberal Party and for prison and social reform, anchoring her work in strongly held Christian beliefs. She also wrote frequently for many women's temperance newspapers and published books on her campaigning travels abroad. It will be shown that her activities in the public sphere both at home and abroad helped the cause of women's emancipation by demonstrating that women can be effective campaigners without threatening the stability of society. She also improved the lot of women by persuading many to abstain from alcoholic drink, thereby facilitating their release from poverty through self help. She helped to shatter the Victorian ideals of sheltered womanhood and by so doing deserves to be remembered.